Detain and Punish : Haitian Refugees and the Rise of the World's Largest Immigration Detention System - Lindskoog, Carl (Book collections on Project MUSE., 2018)
This book provides the first in-depth history of immigration detention in the United States. Employing extensive archival research to document the origins and development of immigration detention in the U.S. from 1973 to 2000, it reveals how the world's largest detention system originated in the U.S. government's campaign to exclude Haitians from American shores, and how resistance by Haitians and their allies constantly challenged the detention regime.